Implementasi Media Visual dalam Pembelajaran Parts of the Body untuk Meningkatkan Kosakata Bahasa Inggris Siswa Kelas III SD - Imelda Sabrina Sibarani; Hanyska Hanyska; Tasya Marlina Napitupulu; Handayani siburian; Bunga Trianda Lubis; Yohana Marpaung; Lilis Sastra Wati Rajagukguk; Monica Elisabeth Bakkara; Putri Ayu Br Torus (Journal of Community Service and Engagement, 2026)
The low mastery of English vocabulary among elementary school students is one of the challenges in the learning process, particularly in the Parts of the Body topic. This community service activity aimed to improve the English vocabulary mastery of third-grade students through the implementation of visual media in interactive learning activities. The implementation method consisted of preparation, material delivery using flashcards, posters, and body-part illustrations, guided practice, educational games, and evaluation through observation and simple exercises. The results showed that the use of visual media improved students’ participation, motivation, and confidence in learning English vocabulary. Students demonstrated better abilities in recognizing, pronouncing, and remembering Parts of the Body vocabulary. Visual media-based learning also created a more active, engaging, and enjoyable learning environment.